Investigating the Impacts of Flipbook Media on Middle School Students' Learning Interests in History - Marwan Marwan; Rhoma Dwi Aria Yuliantri (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students learning interests are crucial to the learning process because they influence successful learning outcomes. To achieve this purpose, teachers have to use innovations, such as the use of interactive learning media, to enhance students' enthusiasm for learning. Therefore, this study aims to investigate how employing flipbook learning media impacts students' interest in learning. In this study, 34 students from class VIII of junior high school were chosen randomly as participants, and the data were analyzed using descriptive statistics. The research found that: (1) students who did not use FlipBook media had an average interest of 32.6, falling into the low-interest category; (2) students who did so had an average interest of 46.7, falling into the very high-interest category; and (3) Grade VIII students in junior high school showed a tendency to be more interested in learning about history when using FlipBook media. Based on the test findings, the significance level for the t-test, t-count, and t-table, which are -10.441 1.699, is 0.000 0.05. It was determined that the FlipBook medium positively impacted the Grade VIII students' enthusiasm for learning history. This study has implications for stakeholders, including teachers, students, and others. The findings of this study give teachers different ways of teaching history that will pique their students' attention. Flipbooks may make history lessons more appealing to students, encouraging them to keep learning. The findings of this study are considered by stakeholders as they make policy decisions, particularly in the area of education.